Medicalization of sexual desire - Stegenga, Jacob (2021)
Medicalisation is a social phenomenon in which conditions that were once under legal, religious, personal or other jurisdictions are brought into the domain of medical authority. Low sexual desire in females has been medicalised, pathologised as a disease, and intervened upon with a range of pharmaceuticals. There are two polarised positions on the medicalisation of low female sexual desire: I call these the mainstream view and the critical view. I assess the central arguments for both positions. Dividing the two positions are opposing models of the aetiology of low female sexual desire. I conclude by suggesting that the balance of arguments supports a modest defence of the critical view regarding the medicalisation of low female sexual desire.
Medikalizacija je društveni fenomen u kojem se uvjeti koji su nekada bili pod zakonskom, vjerskom, osobnom ili drugom jurisdikcijom stavljaju u domenu medicinskog autoriteta. Niska seksualna želja kod žena je medikalizirana, patologizirana kao bolest te se tretira nizom lijekova. Postoje dva polarizirana stajališta o medikalizaciji niske ženske seksualne želje: ja ih nazivam mainstream gledištem i kritičkim gledištem. Ocjenjujem središnje argumente za obje pozicije. Ono što dijeli ove dvije pozicije su suprotstavljeni modeli etiologije niske ženske seksualne želje. Zaključujem sa sugestijom da ravnoteža argumenata podržava skromnu obranu kritičkog stajališta o medikalizaciji niske ženske seksualne želje.
Tema broja: Filozofija medicine.
Bibliografske bilješke uz tekst ; bibliografija: str. 30-34.
Abstract ; Sažetak.
Keywords: Filozofija medicine -- Medikalizacija -- Filozofija psihijatrije -- Žene -- Seksualna želja